FOREIGN EXPERIENCE IN FINANCING THE AGRARIAN SPHERE AND DEVELOPMENT OF SCIENTIFIC SUPPLY (American Journal of Business Management, Economics and Banking, 2023)
The article uses the experience of the countries of the Commonwealth of foreign countries and independent states, which have been tested for many years, from research that corresponds to our republic. It can create an opportunity to increase the scientific supply of the agrarian sphere of the country to a high level and to develop agriculture steadily.